GC-MS based metabolite profiling, antioxidant and antimicrobial properties of different solvent extracts of Malaysian Plectranthus amboinicus leaves - Swamy, Mallappa Kumara; Arumugam, Greetha; Kaur, Ravinder; Ghasemzadeh, Ali; Mohd. Yusoff, Mazina; Sinniah, Uma Rani (Hindawi Publishing Corporation, 2017)
This study evaluates the phytochemistry, antioxidant, and antimicrobial effects of Plectranthus amboinicus leaves extracted in different solvents. The methanol extract contained the highest total phenolic ( mg GAE/g) and flavonoid contents ( mg RE/g) and exhibited the highest DPPH scavenging activity (90.13 ± 3.32%) followed by the acetone extract (80.23 ± 3.26%) at 500 μg/mL concentration. Similarly, the highest ferric ion reduction potential ( μM of Fe (II)/g dry weight) was exhibited by the methanol extract followed by the acetone extract ( μM of Fe (II)/g dry weight). The methanol extract showed greater antimicrobial activity against all the tested pathogens (Bacillus subtilis, Methicillin-resistant Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Candida albicans). However, both hexane and acetone extracts failed to inhibit E. coli. S. aureus and C. albicans were more susceptible to all the extracts. Further, GC-MS analysis confirmed the occurrence of a total 46 phytocompounds in different solvent extracts. Some of the major compounds included carvacrol (37.7%), tetracontane (16.6%), squalene (15.6%), tetrapentacontane (13.7%), and Phytol (12.9%). In conclusion, extraction solvents influenced the recovery of phytocompounds and the highest pharmacological activities of the methanol extract could be correlated to the presence of additional bioactive compounds.